Economic growth, banking and financial development: International evidence - Ruíz Porras, Antonio; Rosales Jaramillo, Guillermo (Estudios Económicos de El Colegio de México, 2014)
We study the relationships among economic growth, banking and financial development using dynamic panel-data techniques. The main findings confirm that financial development is positively correlated with growth. They also suggest that banks have indirect and differentiated effects on growth through financial development. Banking concentration and income-cost ratios are positively correlated with financial development; interest net margins are negatively correlated. Furthermore, we quantify the growth imputable to changes in financial intermediation for Argentina, Colombia, Mexico and Peru. We use comparable indicators for 78 economies between 1986 and 2009.